DEVELOPMENT OF 3D WALL MAGAZINE LEARNING MEDIA TO IMPROVE STUDENTS' COGNITIVE UNDERSTANDING OF THE MATERIAL ON THE HISTORY OF THE NATIONAL MOVEMENT FOR CLASS XI SMAN 1 LIRIK: Pengembangan Media Pembelajaran Mading 3D Untuk Meningkatkan Pemahaman Kognitif Siswa Pada Materi Sejarah Pergerakan Nasional Kelas XI SMAN 1 Lirik - Mirza Dwi Sukma Eca; Ahmal; Refli Surya Barkara (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research is a type of Research and Development (R&D) that aims to develop 3D Wall Magazine media to improve students' cognitive understanding of national movement history material in class XI SMA N 1 Lirik. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study consisted of 7 students for the small group trial and 18 students from class XI.3 SMA N 1 Lirik for the large group trial. Data collection instruments included observation, interviews, tests (pretest-posttest), and questionnaires. Data analysis used qualitative and quantitative analysis, including calculations of feasibility percentages and N-gain Scores for media effectiveness.The results showed that the 3D Wall Magazine media is "Very Feasible" to be used in history learning. The assessment from material experts obtained a percentage of 90% and was declared "Very Feasible". The assessment from media experts obtained a percentage of 89% and was declared "Very Feasible". Student responses in the small group trial received a percentage of 81% with the "Very Feasible" category , and in the large group trial, 87% with the "Very Feasible" category.There was an increase in students' cognitive understanding after using the 3D Wall Magazine media, as seen from the pretest and posttest results of both trial groups. In the small group trial, the N-gain score was 0.72 (high category). In the large group trial, the N-gain score was 0.70 (moderate category) , but in the conclusion section, it was categorized as "high". Thus, the 3D Wall Magazine media is quite effective in increasing students' cognitive understanding in the small group trial and effective in the large group trial in increasing students' cognitive understanding of National Movement History material in Class XI.3 SMA N 1 Lirik.